PRE-SERVICE SPORT SPECIALISTS’ PERCEPTIONS OF ACADEMIC INTEGRITY - Fernate, Andra; Smila, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Academic integrity is fundamental value of pre-service sport specialists’ professional competence developing, which promote public confidence in coaching and teaching as a process for professional and personal development. There is an ethical dissonance that the distribution of all dishonesty types was significantly higher than the perception of their legitimacy and that students conduct academic dishonesty despite its perception as unethical (Blau & Eshet-Alkalai, 2017). The research aim is to reveal the pre-service sport specialists’ perceptions of academic integrity and to find out the ways for promotion of academic integrity. The methods: a theoretical analysis of scientific literature, an interpretative phenomenological semi-structured interview, open and axial coding. The research sample 135 pre-service sport specialist, voluntary participants, 47% – female, 53% – male. The main research results: academic integrity perception is important for the development of pre-service sport specialists’ professional competence. Pre-service sport specialists' main opinion about benefit of being academically dishonest is time saving and personal gain. The main causes of academic dishonesty are laziness, lack of knowledge and competence, searching for an easy way.